2021
DOI: 10.1037/per0000460
|View full text |Cite
|
Sign up to set email alerts
|

Location of International Classification of Diseases–11th Revision and Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, dimensional trait models in the alternative five-factor personality space.

Abstract: This study explores the dimensionality (factor analysis) and the relationships (empirical networks) between the Zuckerman alternative five-factor personality model and the two current pathological dimensional personality systems based on the International Classification of Diseases–11th Revision (ICD-11) and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM–5), Section III. To this end, the Zuckerman–Kuhlman–Aluja Personality Questionnaire–Short Form (ZKA-PQ/SF), the Personality Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Note that Anankastia did not correlate with any other categorical PD, so it seems that this clinical usefulness came only from a slight increase in the prediction of Obsessive-Compulsive diagnosis. Given this limited clinical usefulness (as Carnovale et al, 2020, also reported), the high negative correlation with Disinhibition (of both the PID-5-SF and the PiCD), and the large loadings (with the opposite sign) of the Disinhibition and Anankastia domains on the same factor in both factor analyses, the present article supports the redefinition of Anankastia as the opposite pole of the Desinhibition domain (Carnovale et al, 2020;McCabe & Widiger, 2020), although to reach a final conclusion more research will be necessary on the Table 5 b Anankastia domain to explore its clinical correlates and discriminant validity (Aluja et al, 2020).…”
Section: And Mccabe Andsupporting
confidence: 68%
See 1 more Smart Citation
“…Note that Anankastia did not correlate with any other categorical PD, so it seems that this clinical usefulness came only from a slight increase in the prediction of Obsessive-Compulsive diagnosis. Given this limited clinical usefulness (as Carnovale et al, 2020, also reported), the high negative correlation with Disinhibition (of both the PID-5-SF and the PiCD), and the large loadings (with the opposite sign) of the Disinhibition and Anankastia domains on the same factor in both factor analyses, the present article supports the redefinition of Anankastia as the opposite pole of the Desinhibition domain (Carnovale et al, 2020;McCabe & Widiger, 2020), although to reach a final conclusion more research will be necessary on the Table 5 b Anankastia domain to explore its clinical correlates and discriminant validity (Aluja et al, 2020).…”
Section: And Mccabe Andsupporting
confidence: 68%
“…personality correlates of Psychoticism are quite complex and involve different traits (Aluja et al, 2020;García et al, 2020;Zimmermann et al, 2014).…”
mentioning
confidence: 99%
“…Studies on the ICD-11 PD model and its factorial structure suggested using either a five-factor solution or four-factor solutions, resulting in a single low disinhibition/high anankastia domain (38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). In this multidimensional structure, OCPD could be distinguished by a high score on anankastia traits, automatically resulting in low disinhibition traits.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven (11) publications reported on the factorial structure of the ICD-11 PD model, indicating a 4-factor solution (41,42,44,45,(47)(48)(49), a 5-factor solution (46) or both (38,40,43). All of the studies were conducted in either psychiatry samples, general population samples, or both, while the sample size ranged from 162 to 2,522 participants.…”
Section: Factorial Structure Of the Icd-11 Pd Model Regarding Anankasmentioning
confidence: 99%
“…This non‐expected metric of the Social Position variable has been retained because it is the original metric of the index, and to allow for comparisons with examples in the literature where this SPI was used (e.g.,. Aluja, Sayans‐Jiménez, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%